The financial implications of temporary internet restrictions to Mobile Network Operators (MNOs): Evidence from Tanzania's october 29th to november 3rd 2025 event - Ahmed, Issa G. (Priviet Social Sciences Journal, 2026)
This study estimates the immediate financial effects of state-ordered internet restrictions imposed in Tanzania from October 29 to November 3, 2025, amid post-election protests. It addresses a sectoral gap in shutdown-economics research by quantifying the short-run burden on mobile network operators (MNOs) and the associated implications for mobile-money activity and telecom-linked tax revenues. Employing a convergent mixed-methods design, the study combines an event-study analysis of MNO revenue with document analysis of the regulatory framework. Quantitative estimates apply traffic-baseline and ARPU-severity models calibrated to independent network-measurement and contemporaneous reporting that documented a nationwide disruption and sharp suppression of connectivity during the event window. To reflect telecom revenue mechanics, the modelling distinguishes revenue that is relatively fixed over billing cycles (bundles/subscriptions) from revenue that is immediately exposed (usage-based charges, value-added services, OTT bundles) and incorporates likely short-run credits/compensation and enterprise SLA exposure. Findings indicate a conservative, sector-wide revenue shortfall of TZS 18.204 billion (USD 7.4 million) over the six-day window. The disruption also implies TZS 6–12 billion (USD 2.44–4.88 million) in forgone mobile-money fee income and a direct telecom-tax loss of TZS 6.371 billion (USD 2.59 million); including taxes associated with the mobile-money fee base yields an estimated total fiscal shortfall of TZS 8.8–17.6 billion. The study concludes that internet restrictions constitute material economic interventions and highlights a regulatory gap regarding operator cost recovery, recommending proportionality, protection of essential payment rails, and limited cost-sharing/compensation clauses in licensing frameworks